Resource categories and performance in Portuguese non-profit sports clubs - Marco Arraya (BBR: Brazilian Business Review)
The resource-based view (RBV) explores the role of key resources identified as tangible, personnel-based, and intangible resources in creating superior organizational performance. The RBV posits that an organization’s success is mainly driven by resources that possess Barney’s VRIO (valuable, rare, inimitable, and organized) framework. The purpose of this study is to demonstrate the relationship between the three categories of resources and organizational performance. The data was analyzed with a two-stage structural equation modelling approach. The sample included Portuguese sports management staff from non-profit clubs which composed of 375 men and 102 women. The results of the structural model demonstrated that, intangible resources can significantly influence organizational performance while, personnel-based resources influence tangible and intangible resources. The results show that “staff competence”, “reputation”, and “financial capital” were the most essential resources, and that is core for non-profit clubs and their strategy to recognize, develop, and leverage VRIO resources. These findings also have considerable implications for sport managers, and suggestions for possible future research were given.